Role of the economist as official adviser - Johr, W. A.; Singer, H.W. (London, 1955)
The present book owes its origin to a review. While book re views not infrequently estrange scholars, in this case it was a book review which brought together two writers, who pre viously were strangers to each other, to collaborate on a book. The June 1952 number of The Economic Journal published a re view by Dr. H. W. Singer of Professor W. A. Jöhr's Die Beur teilung konkreter wirtschaftspolitischer Probleme. He thought it suitable as an introduction to the techniques and dangers of elucidating problems of economic policy for the economist acting in an advisory capacity to his government on particular measures of economic policy. At the same time, having his own work in mind, he found it deficient in that it failed to deal with the problems and difficulties which confront those working in the economic research divisions of the large international organisations.
Keywords: Economics